2009
DOI: 10.1080/08916930802375729
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of chromatin and not high affinity for dsDNA determines the nephritogenic impact of anti-dsDNA antibodies in (NZB×NZW)F1 mice

Abstract: Recent studies have demonstrated that the nephritogenicity of antibodies to dsDNA and nucleosomes confers to binding of glomerular membrane-associated nucleosomes, and not to cross-reacting glomerular antigens. There is no known parameter that determines antibody pathogenicity aside from specificity for dsDNA/nucleosomes, and systemic lupus erytheomatosus (SLE) patients may have high titer anti-dsDNA antibodies irrespective whether they have lupus nephritis or not. One parameter may be antibody affinity, as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 39 publications
2
24
1
Order By: Relevance
“…In the severe combined immunodeficient (SCID) mice it was confirmed that the binding of human anti-dsDNA AAb to the kidney causes proteinuria and thus tissue damage, probably through different mechanisms [134]. Mjelle et al demonstrated that the availability of glomerular chromatin fragments is prerequisite for renal anti-dsDNA AAb binding [135]. Accordingly, the development of lupus nephritis in humans is strongly associated with high titres of anti-dsDNA AAb [136], which precede the clinical onset of SLE [137] and of disease flares [138].…”
Section: Anti-dsdna Autoantibodiesmentioning
confidence: 93%
“…In the severe combined immunodeficient (SCID) mice it was confirmed that the binding of human anti-dsDNA AAb to the kidney causes proteinuria and thus tissue damage, probably through different mechanisms [134]. Mjelle et al demonstrated that the availability of glomerular chromatin fragments is prerequisite for renal anti-dsDNA AAb binding [135]. Accordingly, the development of lupus nephritis in humans is strongly associated with high titres of anti-dsDNA AAb [136], which precede the clinical onset of SLE [137] and of disease flares [138].…”
Section: Anti-dsdna Autoantibodiesmentioning
confidence: 93%
“…SPR kinetic analyses for unfractionated heparin mixed with nucleosomes at the same molar ratios were performed at 30 l/minute for 180 seconds (association step) followed by 600 seconds of dissociation time. Binding of 163c3 anti-dsDNA mAb (without or with heparin at 1:10 or 1:100 molar ratio) to the DNA chip was analyzed by the kinetic/ affinity assay (35). Regeneration of the chips and all calculations were performed as described (14).…”
Section: Methodsmentioning
confidence: 99%
“…We further analysed anti bodies in sera and glomerular eluates with respect to their specifi city and intrinsic affinity. 99,110 The data were surprisingly clear, and demonstrated that nephritogenic anti-B-DNA antibodies exert their pathogenic effect only when chroma tin fragments are exposed in the mesangial matrix and in the GBM.…”
Section: Lupus Nephritis Pathogenesismentioning
confidence: 95%
“…associated with lupus nephritis, the renal manifestation of this disease. This concept derived from three facts: DNA binds collagen, a component of the glomerular basement membrane (GBM); 98 the nephritogenic antibodies bind DNA; 93,99 and anti-dsDNA antibodies can be eluted from nephritic kidneys. [99][100][101] These facts do not necessarily provide information about the real targets for the antibodies in kidneys in the context of lupus nephritis, only that in vivo-bound IgG antibodies recognize at least DNA.…”
Section: Lupus Nephritismentioning
confidence: 99%
See 1 more Smart Citation